El potencial disruptivo de la narrativa breve de Isaac Rosa sobre la acogida de la migración exterior - Wachowska, Judyta (Studia Romanica Posnaniensia, 2026)
This paper analyzes Isaac Rosa’s short stories “Welcome” and “Rasgos occidentales”, which address external migration. It argues that Rosa’s aesthetics of rupture – estrangement, the questioning of dominant verisimilitude and collective agency drawn from the 15-M movement – disrupts frameworks of social and political plausibility by deconstructing hegemonic discourses and affirming both the right to migrate and the dignified reception of people on the move in today’s humanitarian crisis.